2022
DOI: 10.36937/ben.2022.4707
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Tensile Properties of Asphalt Concrete

Abstract: The tensile strength of asphalt concrete is essential to control the rutting behavior of the pavement. In the present work, asphalt concrete mixtures were compacted at optimum binder content to a target density using roller compaction. Extra mixtures with 0.5 % binder content above and below the optimum were also prepared. Core specimens were extruded from the compacted slab samples for testing. The tensile strength of asphalt concrete was assessed using the indirect tensile strength test and the semi-circular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…It was concluded that using a waste HDPE-modified binder is recommended for improving resistance to moisture-induced damage and adhesion. Sarsam [2] assessed the possibility of implementing extender oil (used oil) and scrap tire rubber to improve the physical qualities of the asphalt cement. It was revealed that a combination of 15% scrap rubber and 10% extender oil provided a suitable control on the softening point, ductility, penetration, and viscosity of the binder.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that using a waste HDPE-modified binder is recommended for improving resistance to moisture-induced damage and adhesion. Sarsam [2] assessed the possibility of implementing extender oil (used oil) and scrap tire rubber to improve the physical qualities of the asphalt cement. It was revealed that a combination of 15% scrap rubber and 10% extender oil provided a suitable control on the softening point, ductility, penetration, and viscosity of the binder.…”
Section: Introductionmentioning
confidence: 99%
“…Asphalt concrete mixture problems were assessed by Mandula and Olexa, (2017) progress in the fatigue life of asphalt concrete mixtures (Sarsam, 2021;Sarsam, 2022a, Sarsam, 2022b. The test results indicated that the phase angle is stabilized after one third of the test duration, while strong increase in the phase angle starts just before reaching the failure point.…”
Section: Introductionmentioning
confidence: 99%